The impact of macroprudential policy on financial stability in selected EU countries (Public Sector Economics - submission site, 2022)
The aim of this paper is to examine the impact of selected macroprudential policy instruments on financial stability. We focus on six euro area economies (Belgium, Cyprus, Germany, Spain, Ireland and the Netherlands) over sixteen quarters (from 2015 Q1 to 2018 Q4) by using the research method of panel econometrics. The following three banking sector aggregate balance sheet variables exhibit the expected impact on credit growth and cyclical fluctuations of the economy: common equity tier one ratio, coverage ratio, and interconnectedness ratio. Moreover, common equity tier one ratio, loan-to-deposit ratio, and leverage ratio exhibit the expected impact on house price growth. Based on our empirical findings, a case can be made for the usage of carefully crafted macroprudential policy instruments that target selected financial and macroeconomic variables with the ultimate goal of attaining the stability of the financial system as a whole.